Evaluasi dan Perancangan User Experience Aplikasi Mobile Registrasi Online Rawat Jalan RSUP Dr. Kariadi menggunakan Human-Centered Design - Muhammad Rikza Ramadhan; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The provision of the mobile application for the online registration of the outpatients in RSUD Dr. Kariadi functions to support the achievement of the Millennium Development Goals (MDGs) and increase the public health status in the implementation of the Technology of Information and Communication in the targeted health sector. The user experience can determine whether a product is successful or failed and determine the performance. It is necessary to evaluate the user experience regularly to make the application function optimally. The method used in this study to analyze the user experience is Human-Centered Design (HCD). The data was taken from the respondents using the USE questionnaire to re-design and fix the user problems in the application. There are four aspects of usability in the USE questionnaire. They are usefulness, ease of use, learning, and satisfaction. These aspects are contained in the 30 statements measured by seven Likert scales. In this research, an initial evaluation was performed to see the range of the usability. Then, the data obtained is used to create a new design of user interface recommendations. A final evaluation is performed to measure the range of the usability on the design of the interface recommendation made. In the initial evaluation, the range of usability obtained was 57,94% which means that the usability is in a good enough category. In the final evaluation, the data of the usability range obtained was 73,79% or in a good category. The result shows that the application's new design has higher usability than the initial application.